2021
DOI: 10.1080/15205436.2021.1968436
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the Dark Side: Exploring Identification with Morally Complex Antagonists

Abstract: This work investigates what factors prompt audience members to engage with morally complex antagonists and examines potential real-world attitudinal outcomes of such engagement. A twopart experimental study (n = 140) examines whether the revelation timing of a character's immoral behavior in a fictional narrative (late reveal versus early reveal) and a person's morality salience (vice salience versus virtue salience) impact identification with a morally complex antagonist. Further, real-world attitudinal outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…While other studies have already shown this effect for character tropes like heroes or villains (Bonus et al, 2021;Tian & Hoffner, 2010), we demonstrate that this is also the case for MACs, who have a special role when it comes to moral behavior. As a lot of research about morality and media characters refers to the ADT, existing research focused on viewers' liking of MACs or their identification with them (e. g., Frazer & Moyer-Gusé, 2023;Raney & Janicke, 2013;Tsay & Krakowiak, 2011). This study expands the existing literature by examining viewers' PSRs as long-term connections with MACs, as PSRs are not limited to exposure and can develop beyond the mediated contact between viewer and media character (Dibble et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…While other studies have already shown this effect for character tropes like heroes or villains (Bonus et al, 2021;Tian & Hoffner, 2010), we demonstrate that this is also the case for MACs, who have a special role when it comes to moral behavior. As a lot of research about morality and media characters refers to the ADT, existing research focused on viewers' liking of MACs or their identification with them (e. g., Frazer & Moyer-Gusé, 2023;Raney & Janicke, 2013;Tsay & Krakowiak, 2011). This study expands the existing literature by examining viewers' PSRs as long-term connections with MACs, as PSRs are not limited to exposure and can develop beyond the mediated contact between viewer and media character (Dibble et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…To better understand this influence, future studies would need to consider recent developments in this research area. For example, the role of moral disengagement in viewers' relationships toward MACs (e. g., Frazer & Moyer-Gusé, 2023;Krakowiak & Tsay-Vogel, 2013), the interdependence of characters (e. g., , or viewers' moral expectancy toward MACs (e. g., N. L. Matthews & Bonus, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations